Photo-stable, 1D-nanofilaments TiO2-based lepidocrocite for photocatalytic hydrogen production in water-methanol mixtures - Badr, Hussein O.; Natu, Varun; Neatu, Stefan; Neatu, Florentina; Kuncser, Andrei; Rostas, Arpad M.; Racey, Matthew; Barsoum, Michel W.; Florea, Mihaela (Matter, 2023)
Water and sunlight are the cleanest, most renewable, and abundant resources on Earth. Developing inexpensive, scalable photocatalysts that are highly stable for hydrogen (H-2) production has long been a cherished dream of humanity. Herein, we report on one-dimensional lepidocrocite-based sub-nanofilaments (NFs), approximate to 5 x 7 & Aring;(2) in cross-section, that generate H-2 from 80:20 v/v water/methanol mixtures when illuminated by simulated sunlight. The NFs were stable in the mixtures for times >4,300 h, 300 h of which were under irradiation. Apparent quantum yields as high as 11.7% were obtained. Based on deuterated water results, we conclude that water is the H-2 source. Further, no carbon dioxide (CO2) due to photocatalytic degradation of methanol was detected. Therefore, the NFs have strong green credentials and lucrative economic prospects for large scale up. We expect these NFs will lead to new lines for developing cheap and ultra-stable materials to produce H-2 photochemically for a long time.